Optical Modulation of Azobenzene‐Modified Peptide for Gold Surface Binding. Issue 20 (16th August 2016) - Slocik, Joseph M.; Kuang, Zhifeng; Knecht, Marc R.; Naik, Rajesh R.
Abstract: The ability to precisely and remotely modulate reversible binding interactions between biomolecules and abiotic surfaces is appealing for many applications. To achieve this level of control, an azobenzene‐based optical switch is added to nanoparticle‐binding peptides in order to switch peptide conformation and attenuate binding affinity to gold surfaces via binding and dissociation of peptides. Abstract : Finding the right wavelength : Optically switchable biomolecular interactions with gold surfaces via conformational changes of a photoswitch built into a peptide are discussed. Exposure to visible light increases peptide binding affinity to gold, while UV light promotes dissociation of peptides.